Extract from a recent letter to Dr. Tracey from Father Corbeil of the Serenje Catholic Mission (International Library of African Music, 1968)
“You advise me in your letter to study the structure of the instruments in my collection. I have already started the drums’ structure and I can now make “ukubamba” (to stretch a skin on a drum) in the bush way. It is not easy. To get the best vibrations of a drum you must find the proper skin which matches with the kind of wood . . . After stretching the skin on the cylinder you have also to find the right time to fix it with straps or wooden pegs ... It is very interesting. Last week, we had 25 visitors here at my museum. Today the teachers following the refresher course at the Serenje Training College, will come in groups to hear something about Zambian culture and music.”
Keywords: African Music